Wizerunek uzdrowicielki syberyjskiej (Natalii Stiepanowej) w świetle krytycznej analizy dyskursu: The image of the Siberian healer in the light of critical discourse analysis - Rybarczyk-Dyjewska, Joanna (Przegląd Wschodnioeuropejski, 2020)
The aim of the article is to present the way in which the Siberian Healer (Natal’ya Ivanova Stepanova), in her publications, creates her own image and, at the same time, encourages to use magic practices proposed by herself. Magic handbooks and compilations of charms written by Stepanova served as the empirical material. They were the basis to describe manipulative and persuasive linguistic activities used to affect the recipient. The most common of those activities is argumentation, which is usually described as ‘a set of actions taken to justify some view’. The healer – in order to sway recipients to her views – mainly uses the so-called fallacious arguments, such as e.g. argumentum ad populum or argumentum ad metum. She also uses specific lexical and stylistic means